Rubisco production in maize mesophyll cells through ectopic expression of subunits and chaperones. (30th April 2021) - Hotto, Amber M; Salesse-Smith, Coralie; Lin, Myat; Busch, Florian A; Simpson, Isabelle; Stern, David B
Abstract : Rubisco is confined to bundle sheath cells in C4 plants, increasing the efficiency of CO2 fixation. Here, we have overcome cell type specificity, adding to the toolkit for engineering photosynthesis. Abstract: C4 plants, such as maize, strictly compartmentalize Rubisco to bundle sheath chloroplasts. The molecular basis for the restriction of Rubisco from the more abundant mesophyll chloroplasts is not fully understood. Mesophyll chloroplasts transcribe the Rubisco large subunit gene and, when normally quiescent transcription of the nuclear Rubisco small subunit gene family is overcome by ectopic expression, mesophyll chloroplasts still do not accumulate measurable Rubisco. Here we show that a combination of five ubiquitin promoter-driven nuclear transgenes expressed in maize leads to mesophyll accumulation of assembled Rubisco. These encode the Rubisco large and small subunits, Rubisco assembly factors 1 and 2, and the assembly factor Bundle sheath defective 2. In these plants, Rubisco large subunit accumulates in mesophyll cells, and appears to be assembled into a holoenzyme capable of binding the substrate analog CABP (carboxyarabinitol bisphosphate). Isotope discrimination assays suggest, however, that mesophyll Rubisco is not participating in carbon assimilation in these plants, most probably due to a lack of the substrate ribulose 1, 5-bisphosphate and/or Rubisco activase. Overall, this work defines a minimal set of Rubisco assembly factors in planta and may help lead to methods of regulating the C4 pathway.